Overexpression of human low density lipoprotein receptors leads to accelerated catabolism of Lp(a) lipoprotein in transgenic mice. - Hofmann, S L (1990)
Lp(a) lipoprotein purified from human plasma bound with high affinity to isolated bovine LDL receptors on nitrocellulose blots and in a solid-phase assay. Lp(a) also competed with 125I-LDL for binding to human LDL receptors in intact fibroblasts. Binding led to cellular uptake of Lp(a) with subsequent stimulation of cholesterol esterification. After intravenous injection, human Lp(a) was cleared slowly from the plasma of normal mice. The clearance was markedly accelerated in transgenic mice that expressed large amounts of LDL receptors. We conclude that the covalent attachment of apo(a) to apo B-100 in Lp(a) does not interfere markedly with the ability of apo B-100 to bind to the LDL receptor and that this receptor has the potential to play a major role in clearance of Lp(a) from the circulation of intact humans.